2021
DOI: 10.1186/s12906-020-03161-6
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of expressive arts-based intervention for young stroke survivors

Abstract: Background Stroke causes lasting brain damage that has numerous impacts on the survivor’s physical, psychosocial, and spiritual well-being. Young survivors (< 65 years old) tend to suffer more because of their longer overall survival time. Expressive arts-based intervention is considered a holistic approach for stroke rehabilitation because it allows participants to express their thoughts and emotions through the arts. The group environment also promotes mutual support among participants. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
(16 reference statements)
0
4
0
1
Order By: Relevance
“…Papers were classified by the type of arts used for rehabilitation: visual arts, music, arts in virtual reality, or therapy programs based on the combined use of various arts (visual arts, music, theater, dance, writing, etc.). Among the 26 studies, we found 8 quantitative studies (reported in Table 1 ), 13 qualitative studies (Carmi and Mashiah, 1996 ; Pachalska et al, 2008 ; Michaels, 2010 ; Beesley et al, 2011 ; Symons et al, 2011 ; Baumann et al, 2013 ; Vija and Lusebrink, 2014 ; Demers and McKinley, 2015 ; Morris et al, 2016 ; Sit et al, 2017 ; Smith et al, 2017 ; Vaudreuil et al, 2019 ), and 5 feasibility studies (Worthen-Chaudharia et al, 2013 ; Morris et al, 2014 ; Ellis-Hill et al, 2015 ; Cucca et al, 2018 ; Chan et al, 2021 ) ( Supplementary material ). We performed a risk of bias analysis on the quantitative studies shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Papers were classified by the type of arts used for rehabilitation: visual arts, music, arts in virtual reality, or therapy programs based on the combined use of various arts (visual arts, music, theater, dance, writing, etc.). Among the 26 studies, we found 8 quantitative studies (reported in Table 1 ), 13 qualitative studies (Carmi and Mashiah, 1996 ; Pachalska et al, 2008 ; Michaels, 2010 ; Beesley et al, 2011 ; Symons et al, 2011 ; Baumann et al, 2013 ; Vija and Lusebrink, 2014 ; Demers and McKinley, 2015 ; Morris et al, 2016 ; Sit et al, 2017 ; Smith et al, 2017 ; Vaudreuil et al, 2019 ), and 5 feasibility studies (Worthen-Chaudharia et al, 2013 ; Morris et al, 2014 ; Ellis-Hill et al, 2015 ; Cucca et al, 2018 ; Chan et al, 2021 ) ( Supplementary material ). We performed a risk of bias analysis on the quantitative studies shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…12 Arts-based programmes (such as 'Stroke Odysseys (SO)' discussed below) are one such approach that shows promising results in enhancing the well-being, self-esteem, social life and rehabilitation experiences of patients with stroke. 13 Indeed, over the past decade, several studies conducted in this patient population have consistently shown a positive impact of different art modalities on psychological (eg, enhancement in confidence and a better sense of control), social (eg, increased social interactions and peer support) and functional (eg, improvement in physical abilities) outcomes. 12 Nonetheless, despite the growing body of research on the benefits of art interventions, the process of scaling-up these interventions, embedding them into healthcare and its associated challenges are not yet well established.…”
Section: Open Accessmentioning
confidence: 94%
“…The evidence summarised above suggests that there is a need for more holistic rehabilitation programmes, especially non-pharmacological and non-invasive modalities, to address the psychosocial needs and improve the quality of life of stroke survivors 12. Arts-based programmes (such as ‘Stroke Odysseys (SO)’ discussed below) are one such approach that shows promising results in enhancing the well-being, self-esteem, social life and rehabilitation experiences of patients with stroke 13. Indeed, over the past decade, several studies conducted in this patient population have consistently shown a positive impact of different art modalities on psychological (eg, enhancement in confidence and a better sense of control), social (eg, increased social interactions and peer support) and functional (eg, improvement in physical abilities) outcomes 12…”
Section: Introductionmentioning
confidence: 99%
“…A study by Cheung and colleagues (2010) found that patients suffering from serious psychiatric illnesses experienced a decrease in psychiatric symptoms after engaging in a drama therapy program [ 27 ]. Storytelling as a component of a creative expression program (CrExp) improves memory and communication skills in patients with mild cognitive impairment (MCI) who are at risk for developing Alzheimer’s disease and dementia [ 28 ].…”
Section: Complementary Medicine and Expressive Arts Therapy In Neuros...mentioning
confidence: 99%